Gendered geographies of environmental injustice - Buckingham, Susan; Kulcur, Rakibe (Antipode, 2009)
As environmental justice concerns become more widely embedded in environmental organizations and policymaking, and increasingly the focus of academic study, the gender dimension dissolves into an exclusive focus on race/ethnicity and class/income. While grassroots campaigning activities were often dominated by women, in the more institutionalized activities of organizations dominated by salaried professionals, gender inequality is neglected as a vector of environmental injustice, and addressing this inequality is not considered a strategy for redress. This paper explores some of the reasons why this may be so, which include a lack of visibility of gendered environmental injustice; professional campaigning organizations which are themselves gender blind; institutions at a range of scales which are still structured by gender (as well as class and race) inequalities; and an intellectual academy which continues to marginalize the study of gender—and women's—inequality. The authors draw on experience of environmental activism, participant observation, and other qualitative research into the gendering of environmental activity, to first explore the constructions of scale to see how this might limit a gender-fair approach to environmental justice. Following this, the practice of “gender mainstreaming” in environmental organizations and institutions will be examined, demonstrating how this is limited in scope and fails to impact on the gendering of environmental injustice.
Keywords: approches et analyses; corps; discipline; environnement; géographie; intersectionnalité; justice environnementale; justice sociale; projet charge mentale; sciences humaines; thématiques

FéminismeS et diversitéS culturelleS - Institut de recherches et d'études féministes (FéminÉtudes, 2009)
Cette publication rend compte des réflexions féministes, théoriques et pratiques majoritaires dans une perspective décoloniale. *** FéminÉtudes est une revue étudiante, féministe et multidisciplinaire. La revue est née en 1995 de l’initiative d’étudiantes féministes dans l’intérêt de partager leurs recherches et de créer un groupe affinitaire. La revue est dirigée par des collectifs de rédaction bénévoles et autogérés, et soutenue par l’Institut de Recherches en Études Féministes (IREF) de l’Université du Québec à Montréal. Au fil des ans, FéminÉtudes a réussi à se bâtir une réputation et une légitimité dans le champ de la recherche en études féministes, tout en offrant une tribune au travaux et aux réflexions de dizaines d’étudiant.e.s. Au-delà de la recherche, c’est également pour l’avancement des luttes féministes que FéminÉtudes souhaite continuer à grandir.
Disponible en libre accès : https://iref.uqam.ca/feminetudes/vol-14-no-1-2009-feminismes-et-diversites-culturelles/
Keywords: 2000 à aujourd'hui; 2000-2009; activisme; amériques; approches et analyses; corps; droits des femmes*; féminétudes; histoire et politique; intersectionnalité; militance; périodes historiques; québec; racisme; ressource en ligne; régions géographiques; systèmes d'oppressions; thématiques; travail; violences; violences contre les femmes*; écriture des femmes*